Time-Restricted Feeding Improves Glucose Tolerance in Rats, but Only When in Line With the Circadian Timing System - de Goede, Paul; Foppen, Ewout; Ritsema, Wayne I. G. R.; Korpel, Nikita L.; Yi, Chun-Xia; Kalsbeek, Andries (Frontiers in Endocrinology, 2019)
Epidemiological studies indicate that shift-workers have an increased risk of type 2 diabetes mellitus (T2DM). Glucose tolerance and insulin sensitivity both are dependent on the circadian timing system (i.e., the time-of-day) and fasting duration, in rodents as well as humans. Therefore, question is whether manipulation of the circadian timing system, for example by changing the timing of feeding and fasting, is a potential preventive treatment for T2DM. Time-restricted feeding (TRF) is well-known to have profound effects on various metabolic measures, including glucose metabolism. However, experiments that directly measure the effects of TRF on glucose tolerance and/or insulin sensitivity at different time points throughout the 24h cycle are lacking. Here we show, in rats, that TRF in line with the circadian timing system (i.e., feeding during the active phase) improves insulin sensitivity during intravenous glucose tolerance tests in the active phase, but not during the sleep phase. Contrasting, TRF out of sync with the circadian timing system (i.e., feeding during the inactive phase) worsened insulin sensitivity, although only marginally, likely because of adaptation to the 4 week TRF regimen. Our results show that TRF can improve insulin sensitivity, but strict adherence to the time-restricted feeding period is necessary, as outside the regular eating hours insulin sensitivity is worsened.